Long-term efficacy of dexamethasone treatment via tympanic antrum catheterization for intractable Meniere's disease - Lyu, Yafeng; Guo, Jia; Li, Xiaofei; Jian, Huirong; Li, Yawei; Wang, Jing; Fan, Zhaomin; Wang, Haibo; Zhang, Daogong (Frontiers in Neurology, 2022)
Objective To explore the long-term efficacy and safety of dexamethasone treatment via tympanic antrum catheterization (TAC) in intractable Meniere's disease (MD). Methods In this retrospective analysis, 60 unilateral intractable MD patients treated with TAC in our hospital from January 2020 to August 2020 were followed for 2 years. Fifty patients who underwent endolymphatic sac decompression (ESD) and 50 patients who accepted intratympanic steroids (ITS) were established as the control groups. Vertigo control, hearing level, tinnitus, aural fullness and functional level were assessed during the study. Results The effective vertigo control rate of intractable MD patients with TAC treatment was 76.7% (46/60) after 2 years follow-up, with a complete control rate of 58.3% (35/60) and a substantial control rate of 18.3% (11/60). The vertigo control rate of TAC was comparable to that of ESD (χ2 = 0.313, p > 0.05), and significantly higher than that of ITS (χ2 = 4.380, p < 0.05). The hearing loss rate of these patients was 10.8% (4/37), which was not significantly different from the control groups (χ2 = 2.452, p > 0.05). The tinnitus improvement rate of patients with TAC was 56.7% (34/60), which was significantly higher than that of patients with ESD (χ2 =11.962, p < 0.001) and ITS (χ2 =15.278, p < 0.001). The aural fullness improvement rate in the TAC group was 56.7% (34/60), which was significantly higher than that in the ESD (χ2 = 11.962, p < 0.001) and ITS groups (χ2 = 5.635, p < 0.05). The functional level improvement rate in the TAC group was 71.7% (43/60), which was much higher than that in the ITS group (χ2 = 17.256, p < 0.001), but there was no significant difference between TAC and ESD (χ2 = 0.410, p > 0.05). No patients had complications or adverse reactions following TAC treatment. Conclusion Dexamethasone treatment via TAC can effectively control vertigo attacks and improve related symptoms of intractable MD patients, providing valuable new insights into the treatment of MD.